Synthesis, Characterization of Ag2s from AgCl Waste of Argentometry Titration with Heating Temperature Variations and Its Application as a Temperature Sensor Based on Negative Temperature Coefficient (NTC) - Gunawan Gunawan; Sarahtrinita Glikeria Like Megawati; Nor Basid Adiwibawa Prasetya; Roni Adi Wijaya (Jurnal Kimia Sains dan Aplikasi, 2022)
Synthesis of Ag2S from AgCl waste of argentometric titration with heating temperature variations as a temperature sensor has been done. This study aims to synthesize Ag2S and examine the effect of heating temperature on crystal quality and electrical characteristics as a temperature sensor based on the Negative Temperature Coefficient (NTC). Ag2S synthesis was carried out by precipitation in a water bath with various heating temperatures of 40°C, 60°C, and 80°C. The success of the synthesis was confirmed by X-Ray Diffraction (XRD) with a typical peak of 2θ from Ag2S standard at 29.07°, 31.60°, 36.97°, 37.81°, and the highest crystallinity was obtained at a heating temperature of 60°C. Meanwhile, UV-Vis Diffuse Reflectance Spectroscopy (DRS UV-Vis) showed a band gap corresponding to Ag2S (0.9-1.05 eV). Furthermore, the Ag2S powder was made into pellets and applied as a temperature sensor. Then the resistance value and the electrical characteristics of the resulting sensor were measured. The best resistance was obtained from Ag2S synthesized at a temperature of 60°C with constant (B) and sensitivity (α) values of 2974 K and −3.35%, respectively. This indicated that Ag2S had been successfully synthesized, and the best sensor quality was obtained from Ag2S heated at a temperature of 60°C.